Decadal intensified and slantwise Subpolar Front in the Japan/East Sea - Chen, Shiyao; Wang, Huizan; Chen, Wen; Zhang, Yun; Zhang, Yongchui (Frontiers in Marine Science, 2022)
The decadal trends in the intensity and position of the Subpolar Front (SPF) in the Japan/East Sea during the time period 1985−2020 are analyzed by using four categories of satellite observed high-resolution sea surface temperature products. The results show that there is a significant intensification trend of the SPF at a rate of 0.37°C/100km/decade. The SPF is further divided into three regions based on the meridional sea surface temperature gradient (MSSTG): the eastern (135−138°E), central (130−135°E) and western (128−130°E) regions, respectively. These three regions showed different meridional movements with the eastern SPF moving poleward by 0.08°/decade, the central SPF moving equatorward by −0.11°/decade and the western SPF showing no significant displacements. The reverse meridional movements between the central and eastern SPF increased its skewness. The frontogenesis rate equation is employed to identify the mechanisms of these decadal trends. Results show that the geostrophic advection term, especially its zonal component, had a crucial role in the decadal trends of the intensity and position of the central and eastern SPF. The decadal trend of the central SPF was mainly attributed to the zonal geostrophic advection of the MSSTG associated with the enhancement of the Subpolar Front Current (SFC) in the upstream region, whereas the decadal trend in the eastern SPF was mainly driven by the zonal geostrophic shear advection controlled by the shear of the SFC in the downstream region. Before 2002, the eastern SPF moved poleward at a rate of 0.27°/decade, whereas there was no obvious trend after 2002. Further decomposition showed that this shift was caused by meridional Ekman advection of the MSSTG.